Shedding light on variational autoencoders - Ruiz Vargas, Jose Cupertino [UNESP]; Novaes, Sergio Ferraz [UNESP]; Cobe, Raphael [UNESP]; Iope, Rogerio [UNESP]; Stanzani, Silvio Luiz [UNESP]; Tomei, Thiago [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Deep neural networks provide the canvas to create models of millions of parameters to fit distributions involving an equally large number of random variables. The contribution of this study is twofold. First, we introduce a diffraction dataset containing computer-based simulations of a Young's interference experiment. Then, we demonstrate the adeptness of variational autoencoders to learn diffraction patterns and extract a latent feature that correlates with the physical wavelength.
Keywords: Fresnel diffraction; Machine Learning; Tensorflow; Variational Autoencoders